DETEKSI DIF PADA BUTIR INSTRUMEN DENGAN PENSKORAN CORRECT SCORE DAN PUNISHMENT SCORE - WARDANI RAHAYU (Jurnal Evaluasi Pendidikan, 2013)
The aim of this study was to determine the number of Differential Item Functioning (DIF) in correct score and punishment score scoring model based on sample size. DIF detection using Lord Chi Square and score equating using sigma and mean method. The amount of DIF scors for each scoring model was obtained from 30 repetition. Data analisis was using two factor Anava. The result of this study was the bigger amount of sample size then the less of DIF score detected using Lord Chi Square in correct score scoring model and the less amount of sample size then the more DIF score detected using Lord Chi Square methode in correct score scoring model